Identification of the Novel Small Compound Stress Response Regulators 1 and 2 That Affect Plant Abiotic Stress Signaling - Seojung Kim; Tae-Houn Kim (Biomolecules)
Abiotic stresses, such as drought, salinity, and extreme temperatures, limit plant growth and development, reducing crop yields. Therefore, a more comprehensive understanding of the signaling mechanisms and responses of plants to changing environmental conditions is crucial for improving sustainable agricultural productivity. Chemical screening was conducted to find novel small compounds that act as regulators of the abiotic stress signaling pathway using the ABA-inducible transgenic reporter line. Small molecules called stress response regulators (SRRs) were isolated by screening a synthetic library composed of 14,400 small compounds, affecting phenotypes such as seed germination, root growth, and gene expression in response to multiple abiotic stresses. Seeds pretreated with SRR compounds positively affected the germination rate and radicle emergence of Arabidopsis and tomato plants under abiotic stress conditions. The SRR-priming treatment enhanced the transcriptional responses of abiotic stress-responsive genes in response to subsequent salt stress. The isolation of the novel molecules SRR1 and SRR2 will provide a tool to elucidate the complex molecular networks underlying the plant stress-tolerant responses.